The vascular role of CGRP: a systematic review of human studies - Al-Karagholi, Mohammad Al-Mahdi; Kalatharan, Veberka; Fagerberg, Peter Schunck; Amin, Faisal Mohammad (Frontiers in Neurology, 2023)
Intravenous infusion of human alpha calcitonin gene-related peptide (h-α-CGRP) has been applied to explore migraine pathogenesis and cerebral hemodynamics during the past three decades. Cumulative data implicate h-α-CGRP in regulating the vascular tone. In this systematic review, we searched PubMed and EMBASE for clinical studies investigating the vascular changes upon intravenous infusion of h-α-CGRP in humans. A total of 386 studies were screened by title and abstract. Of these, 11 studies with 61 healthy participants and 177 participants diagnosed with migraine were included. Several studies reported hemodynamic effects including flushing, palpitation, warm sensation, heart rate (HR), mean arterial blood pressure (MABP), mean blood flow velocity of middle cerebral artery (mean VMCA), and diameter of superficial temporal artery (STA). Upon the start of h-α-CGRP infusion, 163 of 165 (99%) participants had flushing, 98 of 155 (63%) participants reported palpitation, and 160 of 165 (97%) participants reported warm sensation. HR increased with 14%–58% and MABP decreased with 7%–12%. The mean VMCA was decreased with 9.5%–21%, and the diameter of the STA was dilated with 41%–43%. The vascular changes lasted from 20 to >120 min. Intravenous infusion of h-α-CGRP caused a universal vasodilation without any serious adverse events. The involvement of CGRP in the systemic hemodynamic raises concerns regarding long-term blockade of CGRP in migraine patients with and without cardiovascular complications.